Pharmaceutical scope of a phytochemically unexplored medicinal plant, Sarcochlamys pulcherrima (Roxb.) Gaud.: A review - Mazumder, Afjal Hussain; Das, Jayshree; Gogoi, Hemanta Kumar; Paul, Satya Bhusan (Pharmacognosy Reviews)
Sarcochlamys pulcherrima (Roxb.) Gaud. is widely used as traditional medicine and food by different tribes and communities of Assam in India and in neighboring countries. Recent studies conducted in our laboratory showed the broad‑spectrum antimicrobial and antioxidant activities of its crude extract and different solvent fractions and detected the presence of phenolics, flavonoids, saponin, and acidic compounds. This review gives a bird’s eye view of the traditional uses of S. pulcherrima as food and medicine based on the information gathered by personal interaction with the people of different places of Assam as well as the investigations made on its ethno‑botanical claims, biological activities, and other aspects by various workers since years till date and highlight the prospects of future research.
Keywords: Pharmaceutical scope; Sarcochlamys pulcherrima; traditional uses